Perilaku Konsumsi Minuman Tradisional Moke sebagai Determinan Sosial Kejadian Hipertensi pada Laki-laki di Desa Wolodhesa Kecamatan Mego Kabupaten Sikka - Felixculpa Yernal N. Putra (Yayasan Literasi Sains Indonesia, 2024)
Hypertension is a global health issue leading cause of premature death worldwide. Unhealthy eating habits and lifestyle are risk factors for the occurrence of hypertension. Alcohol consumption behavior affects long-term health; alcohol has effects that can increase blood acidity. The purpose of the research is to understand the consumption behavior of traditional moke beverages as a social determinant of hypertension occurrence in men aged 30 to 60 years in Wolodhesa Village, Mego District, Sikka Regency. Type of research uses qualitative research with a phenomenological approach. The number of informants is 8 people. The data collection technique used is in-depth interviews. The research results indicate that the positive perception of the traditional drink is influenced by community traditions, which in turn impacts the high consumption behavior, averaging around 5 liters . The traditional drink plays a role as a medium in customary ceremonies, a welcome drink, and a bond for social relationships. There are positive and negative effects experienced while consuming the traditional drink. The role of community health centers is hindered by societal culture. The family plays a role in shaping positive perceptions regarding the consumption of traditional drinks. It is recommended that the community understands the dangers of excessive consumption of the traditional drink and reduces its consumption. The health center is expected to participate more actively in efforts to change community behavior and collaborate with local leaders, religious figures, and village government. Families are encouraged to instill positive values in their children and support changes in the consumption